Extraction and characterization of phenolic compounds with antioxidant and antimicrobial activities from pickled radish. (February 2020) - Li, Jian; Huang, Shi-Ying; Deng, Qianying; Li, Guiling; Su, Guocheng; Liu, Jingwen; David Wang, Hui-Min
Abstract: The pickled radish can be kept at room temperature for years without spoilage. 2, 6-dihydroxyacetophenone (DHAP), 4-hydroxybenzaldehyde (HBA), and 4-hydroxyphenethyl alcohol (4-HPEA) were first found from the pickled radish. The structures of three phenolic compounds were elucidated by analysis of their nuclear magnetic resonance and high-resolution electro-spray ionization mass spectrometry data. All these phenolic compounds showed good free radical scavenging capacity except HBA. Both DHAP and 4-HPEA also showed high ferric reducing ability. DHAP showed good antimicrobial activity against Escherichia coli, Bacillus subtilis, and Canidia albicans . HBA demonstrated antimicrobial activity against E. coli and C. albicans but not B. subtilis . Based on the results of MTT assay, these compounds did not show cytotoxicity to LO2 cell line. All results indicated the pickled radish had antioxidant and antimicrobial phenolic compounds. To the best of our knowledge, this report is the first to answer partially the question of why pickled foods can be kept at room temperature for years without spoilage based on the evidence of three phenolic compounds. Graphical abstract: Image 1 Highlights: 3 phenolic compounds are purified from the pickled radish for the first time. DHAP displays good abilities of free radical scavenging and ferric reducing power. 4-HPEA has good abilities of free radical scavenging and ferric reducing power. DHAP shows antimicrobial activity against E. coli, B. subtilis and C. albicans. HBA demonstrates antimicrobial activity against E. coli and C. albicans.